Molecular investigations of cat fleas (Ctenocephalides felis) provide the first evidence of Rickettsia felis in Malta and Candidatus Rickettsia senegalensis in Israel. (September 2018) - Hornok, S.; Baneth, G.; Grima, A.; Takács, N.; Kontschán, J.; Meli, M.L.; Suter, V.; Salant, H.; Farkas, R.; Hofmann-Lehmann, R.
Abstract: Rickettsia felis, the causative agent of flea-borne spotted fever, occurs on all continents except Antarctica, owing to the cosmopolitan distribution of its cat flea vector. In this study, cat fleas were collected in two countries where the occurrence of R. felis was either unknown (Malta) or where accurate prevalence data were lacking (Israel). Altogether 129 fleas were molecularly analysed for the presence of rickettsial DNA. On the basis of three genetic markers, R. felis was identified in 39.5% (15/38) of the cat fleas from Malta. Sequences showed 100% identity to each other and to relevant sequences in GenBank. Among the 91 cat fleas from Israel, two (2.2%) contained the DNA of Candidatus Rickettsia senegalensis. Phylogenetically, the R. felis and Candidatus R. senegalensis identified here clustered separately (with high support) but within one clade, which was a sister group to that formed by the typhus group and spotted fever group rickettsiae. This is the first record of R. felis in Malta and of Candidatus R. senegalensis outside its formerly reported geographical range including Africa, Asia and North America.